2000
DOI: 10.1128/iai.68.7.3941-3948.2000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression of Cu/Zn-Containing Superoxide Dismutase from Fasciola hepatica

Abstract: The cytosolic superoxide dismutase (SOD) of Fasciola hepatica, a causative agent of fascioliasis, was purified and characterized. The enzyme consists of two identical subunits, each with an apparent molecular mass of 17.5 kDa. An analysis of the enzyme's primary structure and inhibition studies revealed that the enzyme is a copper/zinc-containing SOD (Cu/Zn-SOD). The enzyme activity was relatively stable in a broad pH range, from pH 7.0 to 10.0, and the enzyme showed maximum activity at pH 7.5. This enzyme als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 54 publications
(58 reference statements)
1
23
0
1
Order By: Relevance
“…Its activity was inhibited by H 2 O 2 and KCN, but not by NaN 3 . These results are comparable with those obtained with other helminth enzymes (Hong et al 1992;Kim et al 2000;Lee et al 2005;Li et al 2005a, b). SeCuZnSOD was determined to be functionally expressed in different developmental stages of S. erinacei, plerocercoid larvae and adult worms.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Its activity was inhibited by H 2 O 2 and KCN, but not by NaN 3 . These results are comparable with those obtained with other helminth enzymes (Hong et al 1992;Kim et al 2000;Lee et al 2005;Li et al 2005a, b). SeCuZnSOD was determined to be functionally expressed in different developmental stages of S. erinacei, plerocercoid larvae and adult worms.…”
Section: Discussionsupporting
confidence: 82%
“…They play essential roles in protecting organisms from oxidation by the superoxide anion which is produced by enzymatic and non-enzymatic metabolic pathways (Fridovich 1998). SODs have been identified and characterized in various helminth parasites, and their essential roles for parasite survival in the hosts have been well addressed (Henkle et al 1991;Hong et al 1992;HenkleDührsen et al 1995;Kim et al 2000;Tawe et al 2000;Castellanos-González et al 2002;Lee et al 2005;Li et al 2005a, b;Wu et al 2008). Several studies have also suggested the potential of SODs of parasitic helminths as vaccine candidates (Shalaby et al 2003;Carvalho-Queiroz et al 2004;Cook et al 2004;Vaca-Paniagua et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…SODs have been demonstrated from various helminths of different species such as Schistosoma mansoni, Onchocerca volvulus, Dirofilaria immitis, Brugia pahangi, and F. hepatica (Callahan et al 1991;Hong et al 1992;James et al 1994;Kim et al 2000;Thorpe 1965). Infection with F. hepatica was accompanied by rising level of the superoxide radicals which opens a way to act as precursor of other ROS (Abo-Shousha et al 1999;Oberley and Oberley 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Degenerate oligonucleotide primers (CZ-Df/CZ-Dr for Cu/ZnSOD and Mn-Df/Mn-Dr for MnSOD, Table 1) were designed based on two highlyconserved regions of Cu/ZnSOD or MnSOD cDNA sequences of other species Henkle-Duhrsen et al 1995 ;Kim et al 2000). PCR reactions were performed on C. sinensis cDNA library.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%